Products of Dental Use Containing Copaiba Oil-resin: Technological Prospecting Based on Patents - Valadas, Lidia A. R.; de Oliveira-Filho, Rosueti Diógenes; de Oliveira, Marcelo Bruno Lemos; de Mello Fiallos, Ana C.; Lotif, Mara Assef Leitão; de França Fonteles, Marta Maria; Bandeira, Mary Anne Medeiros (Recent Patents on Biotechnology, 2020)
Background: Copaiba oil-resin has been widely used and is especially found in neotropical regions, for which several pharmacological activities have been documented over the years. Prospective studies in intellectual property banks are important to increase competitiveness and thus generate new products in various research areas. Objective: A prospective study was carried out on patents of products containing copaiba oil-resin for dental use in intellectual property banks. Methods: The research was conducted with patent searches in six intellectual property banks of the world. Relevant information about the invention in the patent document was collected, processed and described. Results: The search found 9 patents using copaiba resin oil-resin in dental products. The National Institute of Industrial Property (INPI-Brazil) had the highest number of deposits (5), followed by Espacenet (2) and Free Patents (2). C. Langsdorffii was highlighted as the most widely used species in the products and deposits of vehicles in formulations (3). All the patents in the search are A61K code for medical, dental or hygienic purposes. Conclusion: Most of the found patents are related to the area of Microbiology, specifically with application in Cariology. Brazil is represented by the INPI and presented the highest number of patent applications when compared to other intellectual property banks.
Keywords: cariology